Existence and Ulam Stability of Solutions for Discrete Fractional Boundary Value Problem - Fulai Chen; Yong Zhou (Discrete Dynamics in Nature and Society)
We discuss the existence of solutions for antiperiodic boundary value problem and the Ulam stability for nonlinear fractional difference equations. Two examples are also provided to illustrate our main results.